Hydrochemical properties of groundwater samples in the Bayat Melange Complex, Klaten, Indonesia - Thomas Triadi Putranto (PANGAEA, 2017)
The Geological setting of Bayat that has a complexity in structural geology as well as a variety of lithology cause this region is interesting to be investigated from the hydrogeological point of view. Hydrogeological assessments were conducted based on the hydrogeological and geological mapping, as well as hydrochemical analysis. Groundwater level measurements were carried out at 51 measurement points. There were 25 groundwater samples to analyse ion content using Ion Chromatography and ICP-OES. There are 7 lithology units, Schist-phyllite-marble, Nummulities limestone, Diorite intrusion, Pebbly sandstone, Layered limestone, Colluvial and Alluvial deposits.
Supplement to: Putranto, Thomas Triadi; Hidajat, W K; Wijaya, H (2017): Hydrochemical assessment of unconfined aquifer system in bayat melange complex, Klaten, Indonesia. International Journal of GEOMATE, 13(39), 17-24, https://doi.org/10.21660/2017.39.17336